Renomegaly and acute kidney injury as primary manifestations of non-Hodgkin's lymphoma: a report of three cases - Yu Bai; Yuanyuan Zheng; Qidong Zhang; Qun Jiang; Zongli Diao; Wang Guo; Sha Liu; Wenhu Liu (BMC, 2023)
Abstract Background In adults with non-Hodgkin's lymphoma, renal enlargement and acute kidney injury occur infrequently at first presentation, especially in T lymphocytic lymphomas. Case presentation We report three cases of non-Hodgkin's lymphoma with acute renal injury and bilateral renal enlargement. At diagnosis, one patient presented with an adrenal mass, one patient's lymph node biopsy was consistent with a renal biopsy, and one patient had primary renal lymphoma with no extrarenal disease. Assessment of renal pathology in Case 2 and Case 3 showed interstitial lymphocyte infiltration; the pathological types were non-Hodgkin's diffuse large B lymphoma originating from activated B cells outside germinal centers and non-Hodgkin's T-lymphoblastic lymphoma/leukemia, respectively. Case 1 did not receive anti-lymphoma therapy and died from infection and multiple organ failure within 1 month of hospitalization. Case 2 received eight courses of R-CHOP; her lymphoma recurred 2 years after diagnosis and she died from severe pulmonary infection 3 years after diagnosis. Case 3 received hyper-CVAD regularly and achieved stable renal function; this patient remains under follow-up. Conclusions Renal lymphoma may have diverse manifestations, especially primary renal lymphoma without extrarenal involvement. Nephrologists should pay careful attention to these manifestations to ensure accurate diagnosis.